2011
DOI: 10.1261/rna.2552811
|View full text |Cite
|
Sign up to set email alerts
|

Structural implications into dsRNA binding and RNA silencing suppression by NS3 protein of Rice Hoja Blanca Tenuivirus

Abstract: Rice Hoja Blanca Tenuivirus (RHBV), a negative strand RNA virus, has been identified to infect rice and is widely transmitted by the insect vector. NS3 protein encoded by RHBV RNA3 was reported to be a potent RNAi suppressor to counterdefense RNA silencing in plants, insect cells, and mammalian cells. Here, we report the crystal structure of the N-terminal domain of RHBV NS3 (residues 21-114) at 2.0 Å . RHBV NS3 N-terminal domain forms a dimer by two pairs of a-helices in an anti-parallel mode, with one surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…The only hit with a Z-score of Ͼ5 was the N-terminal domain of protein NS3 from rice hoja blanca tenuivirus (Table 3). NS3 suppresses RNA interference pathways in host cells by binding to both siRNA and miRNAs (29,30). Although these proteins superimpose with r.m.s.d.…”
Section: Structure Of the Cdia-ct/cdiimentioning
confidence: 99%
“…The only hit with a Z-score of Ͼ5 was the N-terminal domain of protein NS3 from rice hoja blanca tenuivirus (Table 3). NS3 suppresses RNA interference pathways in host cells by binding to both siRNA and miRNAs (29,30). Although these proteins superimpose with r.m.s.d.…”
Section: Structure Of the Cdia-ct/cdiimentioning
confidence: 99%
“…RHBVp3, as well as p19 of tomato bushy stunt virus (TBSV) (Ye et al, 2003), also binds the siRNA duplexes in a size-dependent mode. A crystal structural analysis of RHBVp3 revealed that the N-terminal domain of RHBVp3 forms a dimer by two pairs of ␣-helices and that the structure plays an important role in binding to the siRNA duplexes (Hemmes et al, 2007Yang et al, 2013).…”
Section: Q2mentioning
confidence: 99%
“…VSRs, including the p3 protein of RSV and RHBV, can bind to the siRNA duplex (Mérai et al, 2006;Lakatos et al, 2006;Hemmes et al, 2007;Xiong et al, 2009;Yang et al, 2013). To determine whether RGSVp5 can bind to siRNA, we performed several gel mobility shift assays.…”
Section: Sirna Binding Activity Of Rgsvp5mentioning
confidence: 99%
“…NS3 was shown to form a dimer in solution and specifically bind to 21 nt dsRNA with high binding affinity (Hemmes et al, 2007(Hemmes et al, , 2009. 10C) (Schnettler et al, 2008;Yang et al, 2011). However, the crystal structure of the N-terminal domain (NTD) of RHBV NS3 (residues 21-114 amino acids) was determined.…”
Section: (A) Sirna Duplex Sequestrationmentioning
confidence: 99%